Screening and Identification of Lujo Virus Entry Inhibitors From an Food and Drug Administration-Approved Drugs Library - Cao, Junyuan; Dong, Siqi; Liu, Yang; Zhou, Minmin; Guo, Jiao; Jia, Xiaoying; Zhang, Yueli; Hou, Yuxia; Tian, Ming; Xiao, Gengfu; Wang, Wei (Frontiers in Microbiology, 2021)
The Lujo virus (LUJV) belongs to the Old World (OW) genus Mammarenavirus (family Arenaviridae); it is categorized as a biosafety level (BSL) 4 agent. Currently, there are no U.S. Food and Drug Administration (FDA)-approved drugs or vaccines specifically for LUJV or other pathogenic OW mammarenaviruses. Here, a high-throughput screening of an FDA-approved drug library was conducted using pseudotype viruses bearing LUJV envelope glycoprotein (GPC) to identify inhibitors of LUJV entry. Three hit compounds, trametinib, manidipine, and lercanidipine, were identified as LUJV entry inhibitors in the micromolar range. Mechanistic studies revealed that trametinib inhibited LUJV GPC-mediated membrane fusion by targeting C410 (located in the transmembrane (TM) domain), while manidipine and lercanidipine inhibited LUJV entry by acting as calcium channel blockers. Meanwhile, all three hits extended their antiviral spectra to the entry of other pathogenic mammarenaviruses. Furthermore, all three could inhibit the authentic prototype mammarenavirus, lymphocytic choriomeningitis virus (LCMV), and could prevent infection at the micromolar level. This study shows that trametinib, manidipine, and lercanidipine are candidates for LUJV therapy, and highlights the critical role of calcium in LUJV infection. The presented findings reinforce the notion that the key residue(s) located in the TM domain of GPC provide an entry-targeted platform for designing mammarenavirus inhibitors.